Managing Water Resources under Climate Uncertainty : Examples from Asia, Europe, Latin America, and Australia - Shrestha, Sangam; Anal, Anil K.; Salam, P. Abdul; van der Valk, Michael (Springer Water, 2015)
The availability of clean water is a major global challenge for the future due to a rapidly growing population and urbanization where further stress in water resources is expected due to the impact of climate change. The wide range of impacts includes for example changes in hydrology, moisture availability, spatial and temporal variations in magnitude of stream flow, and dwindling of water levels with adverse effect on wetlands and ecosystems. As a consequence, water management has become a serious issue and was identified as a global societal challenge. Climate change forecasting is one of the key issues in recent research on sustainable water resources management. This book aims to come up with views to address the queries of planners, policymakers, and general people for water resources management under uncertainty of climate change, including examples from Asia and Europe with successful adaptive measures to change the challenge of climate change into opportunities.